An Analysis Teacher’s Question in English Learning at Second Grade in MTsN 3 Kota Pariaman - Rifqa, Haniifatul; Syahrul, Syahrul; Reflinda, Reflinda; Melani, Melyann (ALSYS, 2023)
This research was due to some problems that was found in MTsN 3 Pariaman. Frist, most of the students did not response the teacher’s question. Second, most of the students were passive in the classroom. Third, the students’ did not answer the questions that require their critical thinking. This research aimed to find out the the type of question that asked by the teacher, the higher order thinking the teacher’s question, and the lower order thinking the teacher’s question. The researcher used qualitative research design. The key informants of this research are English teacher of eighth grade of MTsN 3 Pariaman. Mean while for the supporting informant, the researcher use snowball sampling.In this research, the researcher used 2 instruments which are observation and interview.The interview that was used was structured interview where the researcher prepares the question before conducting the interview. Based on the finding of the result, the researcher concluded that there are some types of questions that were asked by the teacher. First, question begin with “what”. The “what” questions that were asked was mostly LOTS question since the students did not need to give critical or high thinking answer to solve the questions that were asked. Second, convergent question or questions that only require “yes” or “no” answer which frequently place an emphasis on the recollection of previously taught material rather than requiring pupils to engage in higher-level thinking in order to come up with an answer. Third, questions that he already know the answer. This was used to checking students' knowledge and monitor classroom management. Last, referential questions or question that the teacher does not know the answers, and require long syntactically complicated answers. This question was to give students the opportunity to freely express their thoughts and generate output in the target language.